Adaptations to Post-exercise Cold Water Immersion: Friend, Foe, or Futile? - Ihsan, Mohammed; Abbiss, Chris R.; Allan, Robert (Frontiers in Sports and Active Living, 2021)
In the last decade, cold water immersion (CWI) has emerged as one of the most popular post-exercise recovery strategies utilized amongst athletes during training and competition. Following earlier research on the effects of CWI on the recovery of exercise performance and associated mechanisms, the recent focus has been on how CWI might influence adaptations to exercise. This line of enquiry stems from classical work demonstrating improved endurance and mitochondrial development in rodents exposed to repeated cold exposures. Moreover, there was strong rationale that CWI might enhance adaptations to exercise, given the discovery and central role of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) in both cold- and exercise-induced oxidative adaptations. Research on adaptations to post-exercise CWI have generally indicated a mode-dependent effect, where resistance training adaptations were diminished, whilst aerobic exercise performance seems unaffected but demonstrates premise for enhancement. However, the general suitability of CWI as a recovery modality has been the focus of considerable debate, primarily given the dampening effect on hypertrophy gains. In this mini-review, we highlight the key mechanisms surrounding CWI and endurance exercise adaptations. The review also highlights and reiterates the potential for CWI to enhance endurance performance, with support from classical and contemporary works. Lastly, this review discusses the implications and insights (with regards to exercise adaptations) gathered from recent studies examining the longer-term effects of CWI on training performance and recovery.